"No one associates alcohol with being in good health": Health and wellbeing as imperatives to manage alcohol use for young people. Issue 2 (26th February 2021) - Caluzzi, Gabriel; MacLean, Sarah; Livingston, Michael; Pennay, Amy
Abstract: Young people's drinking has declined markedly in Australia over the past 15 years, and this may be linked to changing norms and values around health. We take the view that healthism—a discourse that privileges good health and renders people personally responsible for managing health—has become pervasive, creating new pressures influencing young people's alcohol practices. Through interviews with 50 young light drinkers and abstainers, we explored these notions of health and alcohol. Although health was not the only reason that participants abstained or drank lightly, many avoided drinking to minimise health risks and to pursue healthy lifestyles. Their understanding of health came from multiple sources such as the media, schools, parents—and often reinforced public health messages, and healthist discourse. This discourse influenced how participants perceived health norms, engaged with health in everyday life and managed their alcohol consumption. Because the need to be healthy incorporated bodily health, mental health and social wellbeing, it also created tensions around how young people could drink while maintaining their health. This highlights the importance of health as a key consideration in the alcohol practices of light drinking and abstaining young Australians, which could help explain broader declines in youth drinking.